(untitled) (Confluenţe Bibliologice, 2023)
The article gives a selection of significant passages from the work of the honorary member of the Romanian Academy Nicolae Stoicescu, which demonstrates the need for struggle against right and left opportunism to strengthen unity of the Romanian language in various historical confrontations.